When love is jeopardized: Governing online love scams in Malaysia - Kamaruddin, Saslina; Wan Rosli, Wan Rosalili; Abd Rani, Ahmad Ridhwan; Md Zaki, Noor Zira Azlin; Omar, Mohd Faizal (Science and Engineering Research Support Society, 2020)
In this era of globalization, the way people communicate and build relationships have evolved from the real world to cyberspace. The Internet creates opportunities for users to find romance and have affairs with people anywhere in the world. Due to this, apart from finding true love, many fall prey to the hands of scammers that aims to cheat another for money and even reputation. Last year, it was reported that more than sixty-eight million ringgit was loss due to romantic scams and the most targeted victims are lonely and elderly women. The main objective of this study the typology and the modus operandi of love scams. The paper would also analyze the existing problems in the current legal framework governing love scams and aims identify the loopholes within the current legislation in dealing with the problem. A doctrinal legal research method will be used in this article. The author contends that the scattered legal and regulatory landscape has contributed to the growing cases of love scam and thus, reform is needed to effectively govern the crime. In addition, the governance of cyber security can also be improved with the advancement of analytic tool to combat love scam in Malaysia.